EFFECT OF FOREIGN DIRECT INVESTMENT ON THE UNEMPLOYMENT RATE IN IRAQ AFTER 2003 - Dr. Iqbal Hashem Mutashar AL-Lami; Dr. Afiefa B. Showket AL-Lami; Dr. Ahmed Iyad Ibrahim (Scholars Digest Publishing, 2024)
Foreign direct investment is an important means of activating all economic sectors and thus increasing employment opportunities. The research aims to determine the degree of influence exerted by the flow of foreign direct investment on unemployment rates after 2003, specifically for the period 2003–2020, and to study the costs and benefits of foreign direct investment, identifying the strengths and weaknesses that affect attracting foreign investments, and evaluating foreign participation and its impact on employment by highlighting the relationship between foreign direct investment and unemployment rates. The research adopted a descriptive analytical approach using standard methods based on the longitudinal time series model panel data and according to the EViews 10 statistical program, verifying the extent of the effect between the independent variable and the dependent variable (unemployment). The research hypotheses about the positive effect of attracting investments on reducing unemployment rates have been tested, and it has been proven that there are many obstacles facing foreign investments in Iraq. The most important finding of the research is that the independent variable (foreign investment) is of increasing positive importance in terms of providing services and generating job opportunities.
Keywords: foreign direct investment flow, unemployment rates, investment environment, attracting investors, investment climate, local labor force.